2013
DOI: 10.1093/nar/gkt1345
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure and tandem DNA recognition of the C-terminal effector domain of PmrA from Klebsiella pneumoniae

Abstract: Klebsiella pneumoniae PmrA is a polymyxin-resistance-associated response regulator. The C-terminal effector/DNA-binding domain of PmrA (PmrAC) recognizes tandem imperfect repeat sequences on the promoters of genes to induce antimicrobial peptide resistance after phosphorylation and dimerization of its N-terminal receiver domain (PmrAN). However, structural information concerning how phosphorylation of the response regulator enhances DNA recognition remains elusive. To gain insights, we determined the nuclear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
4
31
0
Order By: Relevance
“…On the other hand, the DNA-bound structure of PhoB DBD has for a long time been the only source of information for structural changes of the DBD upon binding to DNA (21). Recently, the structures of K. pneumoniae PmrA DBD and E. coli KdpE bound to their respective cognate DNA sequences have been solved (22,56). Although PhoB, PmrA and KdpE belong to the same OmpR/PhoB subfamily, their DBDs have shown very different structural and functional characteristics when bound to DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the DNA-bound structure of PhoB DBD has for a long time been the only source of information for structural changes of the DBD upon binding to DNA (21). Recently, the structures of K. pneumoniae PmrA DBD and E. coli KdpE bound to their respective cognate DNA sequences have been solved (22,56). Although PhoB, PmrA and KdpE belong to the same OmpR/PhoB subfamily, their DBDs have shown very different structural and functional characteristics when bound to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the two DBDs of the OmpR dimer can bind to different DNA sequences in either head-to-tail or head-to-head orientations (18–20), whereas the DBDs of PhoB and PmrA bind to DNA exclusively in a head-to-tail orientation (21,22). Moreover, binding of PhoB to DNA induces bending in the DNA, which is not observed for PmrA.…”
Section: Introductionmentioning
confidence: 99%
“…1). However, our previous NMR study showed that REC amide resonances from BeF 3 À -activated PmrA in complex with DNA are similar to those from the stand-alone BeF 3 À -activated REC dimer 20 , which suggests that the inclusion of DBD and addition of DNA do not greatly change the chemical environment of the PmrA REC dimer. Therefore, the preliminary NMR findings do not agree with the extensive REC-DBD interactions identified in PmrA-1 in the crystal structure.…”
Section: Resultsmentioning
confidence: 88%
“…PmrA was activated by the phosphoryl analogue BeF 3 À , which has been used to activate the REC domain to determine its activated structure 19 . The pmra box on the pbgP promoter of Klebsiella pneumoniae was verified previously 20 , and a series of various-length DNAs covering the half-1 and half-2 sites were mixed with an equal amount of BeF 3 À -activated PmrA for co-crystallization (Supplementary Table 1) to obtain the crystals of complexes with 25-and 26-bp DNA (Supplementary Fig. 3).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation